Determination of In-Vitro Antifungal Activities of Essential Oils Against Fungal Pathogens - Fatma Zehra Ok (Turkish Journal of Agriculture: Food Science and Technology)
This study was carried out to determine the in-vitro antifungal activities of essential oils obtained from thyme (Thymus vulgaris L.), Turkish pickling herb (Echinophora tenuifolia subsp. sibthorpiana), clove (Syzygium aromaticum L.), cinnamon (Cinnamomum zeylanicum Blume), eucalyptus (Eucalyptus globulus Labill), dill (Anethum graveolens L.), juniper (Juniperus communis L.), and ginger (Zingiber officinale Rosc.) against Rhizoctonia solani and Fusarium solani infections. Essential oils were added to autoclaved potato dextrose agar (PDA) medium at 0, 500, 1000 and 2000 ppm doses. Mycelium disks of both fungi with a diameter of 5 mm were transferred to the center of petri dishes and incubated at 24±2 °C for 7 days. The biocontrol efficiencies of the essential oils were calculated by measuring the mycelial development diameters. Essential oil applications showed significant antifungal activity against R. solani pathogen and cinnamon, thyme and clove essential oils at 1000 ppm, and dill essential oil at 2000 ppm doses completely inhibited mycelial development. The biocontrol efficiencies of juniper (2.4-12.6%), eucalyptus (2.8-26.6%) and ginger (18.2-37.3%) essential oils against R. solani were found to be low. While clove and thyme essential oils completely inhibited F. solani mycelial development at 2000 ppm dose, the biocontrol efficiencies of ginger (1.6-3.7%), eucalyptus (1.2-7.4%) and dill (2.9-9.8%) essential oils were low. It was concluded that especially clove, thyme, cinnamon and Turkish pickling herb essential oils showed high in-vitro antifungal activity against both phytopathogens and may have the potential to be used as an alternative to synthetic fungicide active substances.